A Report Trip from Odaesan National Park & Woljeongsa Temple: A Report Trip from Odaesan National Park & Woljeongsa Temple - Musa Kothar Uropmabin (Bali Tourism Board, 2021)
South Korea, 'The Land of the Morning Calm', offers a different experience through a peaceful getaway to the Buddhist temple at Odaesan Mountain for historical tourism enthusiasts. Visiting the Odaesan national park offers various close-to-nature tourism experiences. The 11th South Korea's national Park covers areas spread across Gangneung-si, Hongcheon-gun, and Pyeongchang-gun in Gangwon-do Province??. The Park is a sanctuary for many native Korean animals and plants. Visitors may hike some of the peaks in the area, such as Birobong Peak, Durobong, Dongdaesan and Sogeumgang peaks. For those who would love to witness the country's national treasures, tourists may visit sangwonsa and woljeongsa temple in the vicinity. Woljeongsa and sangwonsa Temples are famous temples in Gangwon Province. It has been a museum for National Treasures of South Korea and cultural properties that recorded part of ancient history. Some of the relics are Dong Jong or Bronze Bell (National Treasure No. 36), Octagonal nine-story Stone Pagoda (National Treasure No. 48), Wooden Seated Child Manjushri of Sangwonsa Temple (National Treasure No. 221) and Documents of Sangwonsa Temple (National Treasure No. 292).